Evaluation of the knowledge and behavior of patients at a university hospital outpatient clinic regarding blood donation - Pirinçci, Edibe; Tuncez, Ayse (My University, 2017)
Aim: This study aims to determine the knowledge, and behavior of patients at a university hospital’s family practice outpatient clinic regarding blood donation.Material and method: In this cross-sectional study, the authors administered a questionnaire to patients (400 people) at the university hospital’s family practice outpatient clinic for three months. The study data were entered into the SPSS packageprogram, and the author performed the statistical analyses using this program.Results: The mean age of the participants was 28.70±10.81. Of them, 86% knew their blood type, and 53.8% had a document showing their blood type. Only 21.8% of the participants had previously donated blood. Blood donation was evaluated accordingto gender; men had offered to donate blood more than women; when evaluated according to marital status those who were married were found to donate blood more than singles. 63.3% of the participants who donated blood said they did so to help other people. Of those who did not donate blood before, 29.1% now consider donating?? In response to the question, how much a person is supposed to weigh in order to donate blood, 47.0% said a person should weigh at least 50 kilograms. When asked how often you could donate blood, 23.8% said every three months.Conclusion: The participants’ attitudes and behavior regarding blood donation were positive. Knowledge of participants is not enough. They are moderately well informed about this issue. People should be continuously provided with training about blood donation to increase their awareness.
Keywords: Genel ve Dahili Tıp; Sağlık Bilimleri ve Hizmetleri